The Effect of Corncob Powder on the Oyster Mushroom Growth (Pleurotus ostreatus) - Sri Yusal, Muh.; Nur, Sri Mukminati (BIOMA: Jurnal Biologi dan Pembelajarannya, 2023)
The oyster mushroom (Pleurotus ostreatus) is classified as a type of wood fungus because most of in rotting wood habitats. Corncob powder is an alternative growing medium for oyster mushrooms to anticipate the scarcity of sawdust. This research aims to examine the corn cob powder effects on the growth of white oyster mushrooms as an alternative to using artificial substrates in mushroom cultivation. The research was carried out at Biology Laboratory of FKIP, Patompo University in October-November 2023. This research was an experimental study using several treatments of corncob powder as a growth medium for F2 oyster mushroom seeds. The research data were analyzed using Analysis of Variance (ANOVA) based on a Completely Randomized Design (CRD) and met the requirements used through the error variance homogeneity test. The results showed corncob powder had a significant effect on the mushroom cap diameter, but did not have a significant effect on the mushroom stem diameter. Doses of 150 & 200 grams are a mixture of corn cob powder that is optimal for growing the diameter of the mushroom cap. Corn cob powder contains carbohydrates, protein, water, ash, cellulose, hemicellose and lignin which are needed for the growth of fungi.